Automating Commonsense Reasoning Using the Event Calculus. - MUELLER, ERIK T. (Communications of the ACM, 2009)
The article discusses the automation of commonsense reasoning, examining the manner in which the field of artificial intelligence will build applications that are more user-friendly and more aware of the world. Commonsense reasoning, the article states, is the human ability to make inferences about properties in the everyday world. Other topics include computational approaches to commonsense reasoning, the use of analogical processing, probability theory, and qualitative reasoning, and methods based on natural language. Also discussed is event calculus.